Video Pembelajaran Berbasis Kearifan Lokal Tri Hita Karana Muatan IPS Tema 7 Subtema 2 - Made Setio Artayana; I Made Tegeh; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2022)
More media still needs to be provided by the school; it impacts low student motivation. In addition, the learning activities provided by the teacher are only guided by textbooks and assignments. This study aims to develop a learning video based on local wisdom Tri Hita Karana on social studies content. This type of research is the development of the ADDIE model. The research subjects were one media expert, a material expert, and a learning design expert. The test subjects were students, totaling 12 students. Methods of data collection with questionnaires and questionnaires. Collection instrument with a rating scale. The analysis technique is descriptive qualitative and quantitative analysis. The study's results assessed the subject matter experts, 98% (very good). The assessment of the lesson design experts is 89.5% (very good). The assessment from media experts is 93.7% (very good). The results of individual tests are 95.1% (very good), and small groups are 96.1% (very good). It was concluded that Tri Hita Karana's local wisdom-based learning video was valid, so it was feasible to use.